Self-perceived Problems in Sleeping and in Self-control Are Related to First Year Study Success in Higher Education - Nije Bijvank, Marije; Tonnaer, Geertje H.; Jolles, Jelle (Frontiers in Education, 2017)
Late adolescents and emerging adults often report lower sleep quality. Recent studies have shown that many of these individuals are also characterized by ongoing development of executive functions, such as self-control and self-monitoring. These functions are not fully mature until later in the twenties. As both suboptimal sleep and improper executive functions can impact academic performance, there could be a relationship between these processes. However, few studies have examined these relationships simultaneously to more fully understand the effects of sleep on academic performance in higher education. The aim of the present study was therefore to investigate the extent to which sleep quality influences study success in higher education, and to what extent self-perceived executive function influences this possible relationship. A large survey was conducted among 1760 first-year students at a University of Applied Sciences to evaluate this aim. Results showed that sleep quality and study success are related: lower self-reported sleep quality is related to less study success. A high level of self-control and self-monitoring appears to compensate for the negative effect which sleeping problems have on obtaining study credits. The results of this large-scale study emphasize the need to include sleep and skills in self-control when planning educational innovations aimed at fostering study success in higher education.